O consumidor de baixa renda como uma opção de expansão dos negócios: o caso de uma multinacional de eletroeletrônicos - Chen, Sandra (2006)
There is an important market segment in Brazil represented by low income consumers who are, sometimes, forgotten by big companies. These companies focus their business strategies on high income consumers. In this competitive environment where companies, in general, work, exploiting in a different way the new market segments is an important way to expand or to maintain the market share. This dissertation comprises a case study conducted in a well known multinational consumer electronics company in Brazil, which chose to exploit the low income segment. Specifically in the electronics market, the case study proposes that there is a potential market in the low income segment that is not well exploited by the consumer electronics companies in general. The following theoretical clusters were reviewed such as brand strategies, portfolio analyzes, low income segment and electronics market. The results propose that there are possibilities to exploit the low income market for well known-brand companies that are used to focusing only in the high income segment.